BROCHURE MAKING APPLICATION FOR THE DIGITAL CAFE HANDPHONE USING FLASH LITE 1.1, PHP, MYSQL AND MACROMEDIA FLASH 8 - Mochamad Rasyid Firmansyah; Don Elsyafitra, Skom (Jurnal Sistem Informasi, 2007)
Making digital brochures cafÃ© applications using Macromedia Flash 8 which became thesubject of Scientific Writing is using mobile media to run the application. By usingsimple tools, action scripts and PHP files are used to connect to the server from the cafÃ©,making this application to have any credibility in terms of business promotion andmarketing. Made application allows users to be able to book a place or a reservation touse the online reservation form, and also be able to order food or beverages suppliedthrough a delivery order form.Scientific Writing describes the process of making applications ranging from componentdesign stage, making the scripts, preparation and publication of a flash file server with afacility that has been provided in the software Flash 8.